DEM Analysis of Railtrack Ballast Degradation under Monotonic and Cyclic Loading. (2016) - Qian, Jiangu; Gu, Jianbo; Gu, Xiaoqiang; Huang, Maosong; Mu, Linlong
Abstract: The deformation and the degradation of ballast significantly affect the performance of the railway track. In this study, the discrete element method (DEM) was used to investigate the deformation behavior and degradation characteristics of ballasts under monotonic and cyclic loading. The ballasts were simulated as crushable aggregate which is modeled by bounded discrete elementary particles together and it can be crushed under external forces. The flaw of the aggregate was also modeled by randomly distributed void. Conventional monotonic and cyclic triaxial tests were carried out to investigate the crushing of the aggregates and the associated mechanical behaviors. The effects of confining on the crushing of aggregates and the mechanical behavior were also analyzed. It was found that the permanent deformation of the aggregates significantly increases when particle crushing is considered. The crushing of aggregate is most significant in the first two or three cycles.